How Blockchain Technology Can Benefit Marketing: Six Pending Research Areas - Rejeb, Abderahman; Keogh, John G.; Treiblmaier, Horst (Frontiers in Blockchain, 2020)
The proliferation of sophisticated e-commerce platforms coupled with mobile applications has ignited growth in business-to-consumer (B2C) commerce, reshaped organizational structures and revamped value creation processes. Simultaneously‚ new technologies have altered the dynamics of brand marketing‚ enabling a broader reach and more personalized targeting aimed at increasing brand trust and enhancing customer loyalty. Today‚ the Internet allows marketers to penetrate existing markets, create new online marketplaces and to generate new demand. This dynamic market engagement uses new technologies to target consumers more effectively. In this conceptual paper, we discuss how blockchain technology can potentially impact a firm’s marketing activities. More specifically, we illustrate how blockchain technology can empower the consumer-centric paradigm and foster disintermediation‚ combat click fraud, reinforce trust and transparency, enable privacy protection, empower security and enable creative loyalty programs. We present six propositions that will guide future blockchain-related research in the area of marketing.